Open Data Accessibility Based on Voice Commands - González-Mora, César (2021)
Nowadays, the accessibility of open data on the Web is problematic, in particular for those data enthusiasts (non-technical users really interested in data) with visual disabilities. They generally experience accessibility barriers when browsing open data portals. Therefore, in order to improve accessibility and facilitate visually impaired users to obtain open data, we propose a Web Augmentation Framework for Accessibility for Open Data (WAFRA4OD). The proposed approach uses Web augmentation techniques and voice interaction to help users in finding relevant open data by offering them various useful comments, including a full fledged voice interaction interface. Thereby, WAFRA4OD enables visually impaired data enthusiasts to explore and interact with open data portals using voice commands, and thus improves the accessibility of open data. To show the feasibility of WAFRA4OD we demonstrate its use in a case study using the European Data Portal.